2022
DOI: 10.1038/s41586-022-05385-7
|View full text |Cite
|
Sign up to set email alerts
|

The neurons that restore walking after paralysis

Abstract: A spinal cord injury interrupts pathways from the brain and brainstem that project to the lumbar spinal cord, leading to paralysis. Here we show that spatiotemporal epidural electrical stimulation (EES) of the lumbar spinal cord1–3 applied during neurorehabilitation4,5 (EESREHAB) restored walking in nine individuals with chronic spinal cord injury. This recovery involved a reduction in neuronal activity in the lumbar spinal cord of humans during walking. We hypothesized that this unexpected reduction reflects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
145
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(146 citation statements)
references
References 90 publications
0
145
0
1
Order By: Relevance
“…In support of this, Kathe et al (2022) observed that EES combined with rehabilitation decreased metabolic activity within the lumbar segments in nine participants with various severities of Gate control theory of pain following electrical stimulation. Stimulating large-diameter afferents (blue) via electrical stimulation excites inhibitory interneurons (black) in the substantial gelatinosa.…”
Section: Reorganization Of Descending Pathwaysmentioning
confidence: 68%
“…In support of this, Kathe et al (2022) observed that EES combined with rehabilitation decreased metabolic activity within the lumbar segments in nine participants with various severities of Gate control theory of pain following electrical stimulation. Stimulating large-diameter afferents (blue) via electrical stimulation excites inhibitory interneurons (black) in the substantial gelatinosa.…”
Section: Reorganization Of Descending Pathwaysmentioning
confidence: 68%
“…Spatiotemporal SCS led to an immediate facilitation of walking and a long-term recovery of motor function within 6 months of training in three subjects with chronic incomplete SCI 13 . This approach was recently expanded to a total of nine participants 49 , including three patients with motor-complete SCI implanted with a new electrode array tailored for both leg and trunk motor functions 14 . Overall, these results have created a surge of interest to now integrate SCS into rehabilitation protocols after SCI.…”
Section: Introductionmentioning
confidence: 99%
“…At present, medical science is facing many challenges in early diagnosis and effective treatment of diseases. How to carry out effective diagnosis and treatment of diseases is very important for the improvement of people’s health level ( Cao et al, 2022 ; Diaz et al, 2022 ; Kathe et al, 2022 ; Vistain et al, 2022 ; Xue et al, 2022 ). Smart nanomaterials have received extensive attention in the field of bioengineering and biotechnology due to their unique structural and functional properties.…”
mentioning
confidence: 99%